The Concept of Justice for Prosecutors (Analytical Study of Surah Ali Imran Verse 18) - Irine Dwi Widianingrum (Konsultan Jurnal Ilmiah Indonesia, 2024)
The issue of justice has long been a subject of study both among philosophers and religious scholars, politicians and thinkers or scientists. The question of justice cannot be determined by the measurement used to determine whether something is fair or not. Various answers about justice are usually never or rarely satisfactory so they continue to be debated, thus the formulation of justice is a relative formula. Accompanied by this is a study of the Koran with an exegetical approach. The verses of the Koran are believed to be the words of Allah SWT. And it was revealed to the Prophet Muhammad SAW as a source of information and guidance for humans. The interpretation of Ali Imran's letter discusses various issues. The interpretation of Ali Imran's letter verse 18 relates to the position of people of knowledge. The content of Ali Imran's letter verse 18 factors into the high position of knowledgeable people.